The Relationship Between Sanitation and Clean and Healthy Behavior (PHBS) to Stunting - Miftah Chairani Hairuddin; Fajar Akbar (GLOBAL HEALTH SCIENCE GROUP, 2023)
Indonesia is one of the countries with quite high cases of stunting, making it a serious concern for the government. Stunting must be addressed on multiple levels, not just in terms of nutrition as it is also influenced by inadequate hygiene and unhealthy lifestyle choices. Toddlers who eat unhygienically prepared meals run the risk of contracting infectious diseases. Objective: This study aimed to investigate the between clean and healthy behavior (PHBS) and sanitary conditions on the prevalence of stunting in the Tampa Padang Health Center's operating area. This study used an observational design with a case-control approach. Method: This study was carried out in five villages in the Tampa Padang Health Center's service area. 282 toddlers with stunting served as the study's cases, and 282 toddlers served as controls. Samples were taken froma a proportion of 5 villages so that 282 stunted families were obtained. Then interviews using a questionnaire were carried out to stunted and non-stunted families using simple random. Data from intreviews then analyzed using case control method analysis. sampling. Result: The study's findings demonstrate that the PHBS and Sanitation variables pose no risk of stunting in the Tampa Padang Health Center’s work area since a p-value > 0.05 was obtained from the results of the bivariate analysis with the chi-square test. Conclusion: Sanitation and community PHBS are not risk factors for stunting in the Tampa Padang Health Center’s work area.